2011
DOI: 10.1016/j.jcrs.2010.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Laser in situ keratomileusis flap measurements: Comparison between observers and between spectral-domain and time-domain anterior segment optical coherence tomography

Abstract: Spectral-domain AS-OCT had closer agreement in between-observer and between-instrument measurements than time-domain AS-OCT and provided more consistent measurements of post-LASIK flap thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…4 Optical coherence tomography (OCT) is a noncontact imaging technique that can be used in the post-LASIK assessment of the flap and residual stromal bed (RSB). A recent study 5 found that spectraldomain anterior segment OCT (AS-OCT) provided more consistent LASIK flap measurements than time-domain AS-OCT.…”
mentioning
confidence: 99%
“…4 Optical coherence tomography (OCT) is a noncontact imaging technique that can be used in the post-LASIK assessment of the flap and residual stromal bed (RSB). A recent study 5 found that spectraldomain anterior segment OCT (AS-OCT) provided more consistent LASIK flap measurements than time-domain AS-OCT.…”
mentioning
confidence: 99%
“…It has also been used to quantify changes in the thickness of the crystalline lens with age and accommodation in adult patients. [3][4][5][6][7][8][9][10] Evaluation of the capsular bag containing an IOL by OCT systems was performed before the current Visante system became commercially available. Sacu et al 11 successfully obtained cross-sectional tomograms using a commercially available third-generation Zeiss were comparable to the plastic-embedded histopathologic sections cut from the same specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Other applications of this technology have been described [3][4][5][6][7][8][9][10] ; these include measurements of corneal flaps, evaluation of clear corneal incisions, measurement of the anterior chamber diameter, follow-up of phakic IOL implantation, and evaluation of the anterior chamber angle. The aim of this study was therefore to evaluate the use of AS-OCT in the assessment of postoperative IOL optic changes.…”
mentioning
confidence: 99%
“…SD-OCT is now showing more advantages than time domain OCT which was used in this study for imaging the eye. The results of Hall et al [25] showed that SD-OCT had closer agreement in between-observer and between-instrument measurements than time domain OCT and provided more consistent measurements of post-LASIK flap thickness. If a new full-range SD-OCT is available for imaging the cornea in a 3-dimensional way, DM may be shown more detailed in contour.…”
Section: Discussionmentioning
confidence: 99%